Steganografi untuk Keaslian Tanda Tangan yang Terdigitalisasi Algoritma RC4 - Imam Himawan (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2018)
Steganography for digitalized signature authenticity with the RC4 algorithm (Ron's Code # 4). We use this concept where the text is hidden behind the image and the intended recipient is able to see it. The purpose of this research is to maintain the authenticity of the digitalized signature by hiding the message therein. So that if there is a problem regarding a fake or suspicious signature related to the document, it can be resolved properly using this system, the authenticity of the document can be known. This system uses the RC4 Algorithm made with visual basic 6 programming language. In the steganography method this method is very useful if used on computer steganography because there are many digital file formats that can be used as a medium to hide messages. Commonly used formats include: Image format: bitmap, gif, jpeg, etc., Audio format: wav, voc, mp3, etc., The method used is to insert a message and display the message Technique testing the system with RGB (Red Green Blue) . The quality of the software produced is tested based on fourthe quality characteristics of the ISO 9126 model software, namely functionality, reliability , usability , and efficiency. The results of this study will be documentation in the office PT. Jaya For Current that fits the needs of the company